Effects of a 9-weeks arch support intervention on foot morphology in young soccer players: a crossover study - Hikawa, K.; Tsutsui, T.; Ueyama, T.; Yang, J.; Hara, Y.; Torii, S. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background A flat foot is a common cause of chronic sports injuries and therefore many opportunities for arch support interventions exist. However, young athletes change their foot morphology due to developmental influences even without intervention. Therefore, developmental influences need to be considered when examining the effects of arch support, but there have not been sufficient longitudinal studies to date. This study aimed to determine the effect of the arch support intervention by performing a 9-weeks arch support intervention on the foot morphology and cross-sectional area of the foot muscles in flat-footed young athletes. Thirty-one elementary school boys (Age 11.4 ± 0.5 years, Height 145.2 ± 7.4 cm, Weight 38.8 ± 8.3 kg, BMI 18.2 ± 2.2 kg/m2) with a decreased medial longitudinal arch in the foot posture index were selected as participants from a local soccer club and randomly divided into two groups.